Wandering spleen resulting in gastric volvulus in a child with vanishing gastroschisis: A case report - Chandler A. Annesi; Joseph R. Esparaz; Elizabeth A. Beierle (Elsevier, 2024)
Introduction: Wandering spleen is a rare anatomic finding, either congenital or acquired, that results in hypermobility of the spleen. This paper describes a wandering spleen in a patient with a complex surgical history including vanishing gastroschisis. Case presentation: A 2-year-old female with past medical history of gestational age of 34 weeks, intestinal failure secondary to vanishing gastroschisis, serial transverse enteroplasty (STEP) procedure, and a supplemental nutrition requirement presented with a one-day history of non-bloody, non-bilious emesis, decreased urine output, and decreased oral intake. The vital signs, physical examination and laboratory investigations were normal. Small bowel follow through fluoroscopy study showed no contrast exiting the stomach consistent with gastric outlet obstruction. Patient was taken for exploratory laparotomy and found to have a gastric volvulus secondary to a wandering spleen. At operation, the gastric volvulus was reduced and a splenopexy performed incorporating the use of a mesh bag which was tacked to the abdominal wall in the left upper quadrant. The patient was discharged on POD 4 on their home TPN regimen and enteral feeds were reinstated on POD 14. Conclusion: Wandering spleen as an etiology of gastric volvulus may be seen in patients with a history of gastroschisis. Intraoperative decision making should maintain the goal of splenic salvage and preservation of intestinal length.